Thiazolidinedione or Rhodanine: A Study on Synthesis and Anticancer Activity Comparison of Novel Thiazole Derivatives - Cigdem Ozen; Meltem Ceylan Unlusoy; Nazanin Aliary; Mehmet Ozturk; Oya Bozdag Dundar (Frontiers Media S.A., 2018)
Purpose: A new series of thiazolyl-2,4-thiazolidinedione / rhodanine compounds T1-T23 was synthesized and tested for their anticancer activities. Hepatocellular carcinoma cell lines were chosen due to their strong drug resistance to test the new compounds. Methods: All compounds were synthesized via Knoevenagel Condensation reaction and thiazolidinedione ester compounds (T3,T9,T15,T20) were hydrolyzed for obtaining the acidic compounds (T6,T12,T17,T23). All compounds were firstly screened for their anticancer activity against two hepatocellular carcinoma (HCC) cell lines, Huh7 and Plc/Prf/5 (Plc) cell lines by sulforhodamine B assay. Further IC50 values were calculated for three candidates (T4, T15, T21) in five different HCC (Huh7, Plc, Snu449, HepG2, Hep3B) and one breast cancer (Mcf7) cell line. Results: Compounds T4, T15, T21 had very strong anticancer effects even though their 10 µM concentration in Huh7 cell line. According to IC50 values, T21 was the most effective compound with IC50 values in a range from 2 to 16 µM in 6 cancer cell lines. In terms of cytotoxicity T21 mostly affected Huh7 and interestingly it was less effective against Plc. Conclusions: Considering these results it can be suggested that compounds T4, T15 and T21 may lead to the development of more potent anticancer drugs in the future.   This article is open to POST-PUBLICATION REVIEW. Registered readers (see "For Readers") may comment by clicking on ABSTRACT on the issue's contents page.